2010
DOI: 10.1086/655129
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Transmission to Young Children in a South African Community: Modeling Household and Community Infection Risks

Abstract: Introduction Tuberculosis (TB) transmission is determined by contact between infectious and susceptible individuals. A recent study reported a 4% annual risk of child TB infection (ARTI) in a Southern African township. A model was used to explore the interactions between prevalence of adult TB infection, adult-to-child contacts and household ventilation which could result in such a high ARTI. Methods Number of residents per household and TB incidence were derived from a household census and community TB regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 15 publications
3
54
2
1
Order By: Relevance
“…Argenine also may play a role in elaborate high percentage of nitrous oxide which consider as effective supporting factor to the activated macrophage (Schon et al, 2003;Wood et al, 2010). The present study shown that intra peritoneal infection does result in chronic TB infection in mice organs similar to that observed during low dose aerosol infection mentioned by (Cardona et al, 1999).…”
Section: Advances In Animal and Veterinary Sciences September 2016 | supporting
confidence: 79%
See 1 more Smart Citation
“…Argenine also may play a role in elaborate high percentage of nitrous oxide which consider as effective supporting factor to the activated macrophage (Schon et al, 2003;Wood et al, 2010). The present study shown that intra peritoneal infection does result in chronic TB infection in mice organs similar to that observed during low dose aerosol infection mentioned by (Cardona et al, 1999).…”
Section: Advances In Animal and Veterinary Sciences September 2016 | supporting
confidence: 79%
“…Peanuts are known to be rich in L-arginine and supplementation of nutrition rich in arginin may shorten duration of treatment as well as increase recovery in tuberculosis patients (Schon et al, 2003), Arginine increase nitrogen dioxide level which has a role in stimulating the body defences, patient show shorter duration of cough, increased weight gain and higher seputum conversion rate, all tuberculosis patients had lower levels of plasma L-arginine than healthy one (Wood et al, 2010). Therefor, the aim of this study is to demonstrate the effect of Arachis hypogaea and ethambutol on mice infected with mycobecterim tuberculosis.…”
Section: Advances In Animal and Veterinary Sciences September 2016 | mentioning
confidence: 99%
“…1,9 The current study challenges this notion, suggesting that contact tracing of pediatric cases is as good as the traditional approach. We postulate that because newly diagnosed pediatric TB generally reflects TB transmission within the past year, 10 often from a household contact, 2,11 a pediatric TB case will frequently signify the presence of an undiagnosed infectious case in the household. Furthermore, pediatric cases may have been infected in the community and represent source cases at home, responsible for child-to-adult and child-to-child transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in household transmission could be achieved by increasing ventilation or by separating child and adult sleeping areas. 6 Some important insights into the epidemiology of paediatric TB in high prevalence settings have also been gained through trials of novel TB vaccines. 7 Mahomed et al 8 reviewed the clinical records of all children under 2 years of age diagnosed with TB disease in the greater Cape Town area who were born during a change in the vaccination programme from percutaneous (PC) Tokyo to intradermal (ID) Danish BCG.…”
Section: Advances In Epidemiologymentioning
confidence: 99%